Jane Austen’s Style of Humor in ‘Pride and Prejudice’ - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education, 2025)
Jane Austen’s Pride and Prejudice remains a masterpiece, celebrated for its sophisticated and witty use of humor. Austen’s humor, often subtle and satirical, illuminates societal norms, exposes human folly, and enriches her characters with depth. This article explores Austen’s distinctive style of humor in Pride and Prejudice, focusing on the interplay of irony, wit, and satire. Key elements such as dramatic irony, character-driven humor, and the balance between gentle ridicule and sharp criticism are analyzed. By examining characters like Mr. Bennet, Elizabeth Bennet, and Mr. Collins, we understand how Austen uses humor to critique societal structures such as marriage, class distinctions, and gender expectations. The article also highlights Austen’s strategic use of dialogue, narrative voice, and characterization to infuse humor that is both entertaining and insightful. This analysis underscores the t imelessness of her comedic style and its relevance in contemporary literary studies.